PENGAJARAN PENGARUH TABERNAKEL TERHADAP KESETIAAN BERIBADAH ANAK SEKOLAH MINGGU - Muharoma Chomsatul Farida; Dorce Sondopen (Sekolah Tinggi Teologi Excelsius, 2020)
Abstract: Theoretical Basis: Tabernacle Teaching is a doctrine developed on the basis of biblical teachings. Research objectives: (1) What is meant by the teaching of the Tabernacle based on the Book of Exodus 25: 1-9? How is the effect of teaching (2) How is the application of Tabernacle teaching in the middle class Sunday school of the Pentecostal Church of Christ the Shepherd of the Tabernacle of Surabaya? (3) Tabernacle on the loyalty of children's worship in the middle class Sunday school of the Pentecostal Church of Christ the Shepherd of the Tabernacle in Surabaya? Methods: Quantitative Research Methods and empirical observation approach procedures (Observation). The results of the study: (1) the teaching of the Tabernacle is the human doctrine to find and receive eternal salvation from God through the only way, namely the Lord Jesus Christ. (2) The application of teachers to teach Sunday school children about faith in God, repentance, baptism, testimony, obedience, the fullness of the Holy Spirit, willingness to give, and providing a special place for God through teaching lectures with picture explanations. (3) Tabernacle Teaching Based on the Book of Exodus 25: 1-9 (X) does not have a significant effect on faithful worship. Abstrak: Landasan Teori: Pengajaran Tabernakel adalah doktrin yang dikembangkan berdasarkan ajaran alkitabiah. Tujuan penelitian: (1) Apakah yang dimaksud dengan pengajaran Tabernakel berdasarkan Kitab Keluaran 25:1-9? Bagaimanakah pengaruh pengajaran (2)Bagaimanakah penerapan pengajaran Tabernakel di sekolah minggu kelas madya Gereja Pantekosta Tabernakel Kristus Gembala Surabaya? (3)Tabernakel terhadap kesetiaan beribadah anak di sekolah minggu kelas madya Gereja Pantekosta Tabernakel Kristus Gembala Surabaya? Metode: Metode Penelitian dengan Kuantitatif dan prosedur pendekatan pengamatan empiris (Observasi). Hasil penelitian: (1) pengajaran Tabernakel adalah doktrin manusia untuk menemukan dan menerima keselamatan kekal dari Allah melalui satu-satunya jalan yaitu Tuhan Yesus Kristus. (2) Penerapan guru-guru mengajar kepada anak-anak Sekolah Minggu tentang iman kepada Allah, Pertobatan, Baptisan, Kesaksian, Ketaatan, Kepenuhan Roh Kudus, Kerelaan dalam memberi, dan Menyediakan tempat khusus bagi Tuhan melalui pembelajaran ceramah dengan penjelasan-penjelasan gambar. (3) Pengajaran Tabernakel Berdasarkan Kitab Keluaran 25:1-9 (X) tidak berpengaruh signifikan terhadap Kesetiaan beribadah.